Plasmonic hot electron transport drives nano-localized chemistry - Emiliano Cortés (Nature Portfolio, 2017)
Quantitative understanding of the spatial localization of hot carriers has been elusive. Here Corteset al. spatially map hot-electron-driven reduction chemistry with 15 nm resolution as a function of time and electromagnetic field polarization for different plasmonic nanostructures.